2021
DOI: 10.1067/j.cpradiol.2020.06.009
|View full text |Cite
|
Sign up to set email alerts
|

Current Landscape of Imaging and the Potential Role for Artificial Intelligence in the Management of COVID-19

Abstract: The clinical management of COVID-19 is challenging. Medical imaging plays a critical role in the early detection, clinical monitoring and outcomes assessment of this disease. Chest x-ray radiography and computed tomography) are the standard imaging modalities used for the structural assessment of the disease status, while functional imaging (namely, positron emission tomography) has had limited application. Artificial intelligence can enhance the predictive power and utilization of these imaging approaches and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 42 publications
0
26
0
Order By: Relevance
“…PCR swabs surfaced as abstract instrumentations in discrete COVID-19 diagnostics except for disparate detection accuracy depending on the sample quality, storage, and manual handling ( Shi et al, 2020 ). Medical imaging rose to compensate for PCR tests discrepancies and impede the chain of transmission of COVID-19 ( Shaikh et al, 2020 ). Radiographic imaging modalities contribute to the observation of disease progression ( Greenspan et al, 2020 ) by using radiographic image evidence to support frontline responders in establishing a diagnostic strategy compatible with the presented patient data ( Shi et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…PCR swabs surfaced as abstract instrumentations in discrete COVID-19 diagnostics except for disparate detection accuracy depending on the sample quality, storage, and manual handling ( Shi et al, 2020 ). Medical imaging rose to compensate for PCR tests discrepancies and impede the chain of transmission of COVID-19 ( Shaikh et al, 2020 ). Radiographic imaging modalities contribute to the observation of disease progression ( Greenspan et al, 2020 ) by using radiographic image evidence to support frontline responders in establishing a diagnostic strategy compatible with the presented patient data ( Shi et al, 2020 ).…”
Section: Resultsmentioning
confidence: 99%
“…The biological reproduction stimulates an immune response that damages the lungs and finalizes the evolution of COVID-19. This unique molecular composition attributes the signature biological transmutation of COVID-19 ( Shaikh et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A review on machine learning algorithms in processing medical images regarding the disease can be found in [26] . A review on AI approaches on management of covid-19 can be found in [27] . In [28] , a review on data-driven methods for monitoring, modeling and forecasting the pandemic is presented.…”
Section: Introductionmentioning
confidence: 99%
“…Some articles reviewed only specific type of data set, such as Jalaber et al [ 48 ] set forth with role of CT images to handle COVID-19 suspected patients at large, severity signs and presentation of lesions, and in the end inspected five articles to describe the role of AI for COVID-19 diagnosis. Shaikh et al [ 49 ] investigated AI approaches and landscape of radiographic imaging modalities (CXR, CT and PET) in few articles with limited information about obtained results. Likewise, Dong et al [ 50 ] mainly highlighted CT and PET-CT imaging characteristics presented in different articles and later compared the AI techniques implemented for COVID-19 detection, while Shi et al [ 51 ] accentuated AI approaches to diagnose COVID-19 that segments CXR and CT images.…”
Section: Introductionmentioning
confidence: 99%